Renal-clearable quaternary chalcogenide nanocrystal for photoacoustic/magnetic resonance imaging guided tumor photothermal therapy. (March 2018) - Tan, Longfei; Wan, Jing; Guo, Weisheng; Ou, Caizhang; Liu, Tianlong; Fu, Changhui; Zhang, Qiang; Ren, Xiangling; Liang, Xing-Jie; Ren, Jun; Li, Laifeng; Meng, Xianwei
Abstract: Ultrasmall Cu2 ZnSnS4 (CZTS) nanocrystals with high near infrared (NIR) photothermal conversion abilities and peroxidase-mimic properties are synthesized and functionalized with bovine serum albumin (BSA) for rapid clearance multifunctional theranostic platform. Due to the presence of Cu (I) of CZTS@BSA, H2 O2 could be decomposed to produce highly reactive oxygen species (ROS), catalyzed by intrinsic peroxidase like activity of CZTS. The CZTS@BSA possesses high NIR absorption and excellent photoacoustic (PA) imaging abilities. The as-prepared CZTS@BSA is also reported as an efficient T1 contrast agent for in vivo MR imaging. Therefore, in vivo distribution and rapid renal clearance of CZTS@BSA are successfully tracked by PA/MR dual-modal-imaging and further proved by ICP-MS analysis. Systemic acute toxicity evaluation indicates CZTS@BSA have good biocompatibility to normal tissues and blood. All results reveal that CZTS@BSA could act as a rapid clearance theranostic nanoplatform for dual-modal-imaging guided tumor PTT.